Getting the first birth right: A retrospective study of outcomes for low-risk primiparous women receiving standard care versus midwifery model of care in the same tertiary hospital. Issue 4 (December 2015) - Wong, Nola; Browne, Jenny; Ferguson, Sally; Taylor, Jan; Davis, Deborah
Abstract: Background: There is national and international concern for increasing obstetric intervention in childbirth and rising caesarean section rates. Repeat caesarean section is a major contributing factor, making primiparous women an important target for strategies to reduce unnecessary intervention and surgeries in childbirth. Aim: The aim was to compare outcomes for a cohort of low risk primiparous women who accessed a midwifery continuity model of care with those who received standard public care in the same tertiary hospital. Methods: A retrospective comparative cohort study design was implemented drawing on data from two databases held by a tertiary hospital for the period 1 January 2010 to 31 December 2011. Categorical data were analysed using the chi-squared statistic and Fisher's exact test. Continuous data were analysed using Student's t -test. Comparisons are presented using unadjusted and adjusted odds ratios, with 95% confidence intervals (CIs) and p -values with significance set at 0.05. Results: Data for 426 women experiencing continuity of midwifery care and 1220 experiencing standard public care were compared. The study found increased rates of normal vaginal birth (57.7% vs. 48.9% p  = 0.002) and spontaneous vaginal birth (38% vs. 22.4% p  = <0.001) and decreased rates of instrumental birth (23.5% vs. 28.5% p  = 0.050) and caesarean sections (18.8% vs. 22.5% p  = 0.115) in the midwifery continuity cohort. There were also fewer interventions in this group. No differences were found in neonatal outcomes. Conclusion: Strategies for reducing caesarean section rates and interventions in childbirth should focus on primiparous women as a priority. This study demonstrates the effectiveness of continuity midwifery models, suggesting that this is an important strategy for improving outcomes in this population.